[PP.01.21] HYPERTENSION PREVALENCE, AWARENESS, TREATMENT AND CONTROL IN AMBULATORY TREATMENT-NAÏVE HIV INFECTED PATIENTS IN LILONGWE, MALAWI. (September 2017) - Steffen, H.; Phiri, S.; Heller, T.; Chaweza, T.; Demir, M.; Tweya, H.; Fätkenheuer, G.; Neuhann, F.
Abstract : Objective: In the Malawian national STEPS survey (2009) raised blood pressure (BP) or antihypertensive medication was found in 36.9% male and 29.9% female participants from the general population. Little is known about the prevalence of arterial hypertension in HIV infected (HIV+) patients. As an integrated part of the ongoing prospective LighTen Cohort Study (ClinicalTrials.gov NCT02381275) we aimed at determining hypertension prevalence, awareness, treatment and control in ambulatory HIV+ patients prior to starting antiretroviral therapy (ART) in Lilongwe, Malawi. Design and method: BP values (oscillometric measurement) of adult patients who consented to participate in the study were documented in a standardized fashion together with data concerning known hypertension or antihypertensive medication (treated hypertension). BP of 140/90 mmHg or higher measured during the baseline visit was defined as raised blood pressure (rBP) and controlled hypertension was defined as values below 140/90 mmHg in treated patients. Definite arterial hypertension (dHT) was defined as treated controlled or uncontrolled hypertension or BP of 140/90 mmHg or higher independent of hypertension history during 2 or more measurements on at least 2 occasions within 8 weeks after study inclusion. Results: Data from 1387/1415 HIV+ patients (794 females, 593 males, mean age 36.0 ± 9.3 years) could be analyzed. rBP was found in 256/1387 patients (prevalence 18.5%), dHT was confirmed in only 103 cases for a total prevalence of 7.4% (females 7.7% vs. males 9.3%). Hypertension had been known from medical history in 71 patients, 35 of these patients received treatment (49.3%) and only eight were controlled (11.3%). However, in 22 of 36 untreated patients with a history of hypertension, BP values below 120/80 mmHg were found at the baseline visit. Conclusions: Information from medical history concerning hypertension seems to be considerably flawed. In view of possible drug-drug interactions with ART a strictly defined diagnosis of arterial hypertension is mandatory prior to starting antihypertensive treatment in HIV+ patients. Systematic measurements and documentation of arterial blood pressure and integrated patient instructing and educating programs at HIV centers may be helpful in order to assure hypertension diagnosis as well as improved treatment and control rates in Malawi.